2017
DOI: 10.1097/meg.0000000000000787
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rectal indomethacin, diclofenac, and naproxen for the prevention of post endoscopic retrograde cholangiopancreatography pancreatitis

Abstract: Diclofenac and indomethacin patient groups had a lower incidence of PEP than the naproxen group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“… 25 Furthermore, among the NSAIDs, diclofenac was acted better than indomethacin 24 and naproxen. 26 Howbeit some controversies have existed about the superiority of diclofenac against other NSAIDs. 25 - 27 We also previously in a double-blind RCT reported that single suppository dose of 500 mg naproxen, as another member of NSAIDs, immediately before ERCP decreased the rate of PEP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 Furthermore, among the NSAIDs, diclofenac was acted better than indomethacin 24 and naproxen. 26 Howbeit some controversies have existed about the superiority of diclofenac against other NSAIDs. 25 - 27 We also previously in a double-blind RCT reported that single suppository dose of 500 mg naproxen, as another member of NSAIDs, immediately before ERCP decreased the rate of PEP.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Howbeit some controversies have existed about the superiority of diclofenac against other NSAIDs. 25 - 27 We also previously in a double-blind RCT reported that single suppository dose of 500 mg naproxen, as another member of NSAIDs, immediately before ERCP decreased the rate of PEP. 28 Based on all of the above mentioned shreds of evidence, it seems that rectal NSAIDs are effective and safe in the prevention of PEP in all levels of risk.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one clinical trial 42 has directly compared the efficiency of rectal indomethacin and diclofenac in the prevention of PEP among unselected patients. However, in that study, PEP was defined as a more than 300% increase in amylase and lipase levels compared with the baseline value, with a less than three‐fold increase in the upper normal limit levels, 24 h after the procedure, accompanied by abdominal pain, leading to prolonged hospitalization 42 . This definition is not in conformance with the consensus criteria of acute pancreatitis and differs from the standard definition used in the RCTs included in our meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Levenick et al in patients at average risk of ERCP showed that rectal NSAIDs may not have prophylactic benefits in average-risk patients [13]. Among NSAIDs, diclofenac and indomethacin are more effective than naproxen in PEP prophylaxis [15]. The administration route is also significant as NSAIDs administered via the rectal route effectively prevents PEP [7,9,11,12].…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%